Model Konseling Kelompok Teknik Expresif Writing Berlandaskan Falsafah Dandang Tingang Untuk Meningkatkan Perilaku Respect - Karyanti Karyanti; Muhammad Andi Setiawan (JURKAM: Jurnal Konseling Andi Matappa, 2018)
The purpose of this research is (1) to know how the implementation of expressive writing group counseling based on the philosophy of tinggang, (2) to find the model design counseling group expressive writing technique with flasafah dandang tingang to improve the respect behavior.Research method used is Research and Development (R&D). The result of the model development that has been done by the researcher then design a model that contains (1) Rational, (2) Objectives, (3) Assumptions, (4) Target intervention, (5) Component model, (6) Model steps, 7) Materials, (8) Means, (9) Evaluation and indicators of success. The model that has been compiled is tested to determine the effectiveness of the model that has been compiled. The result of the experiment showed that group counseling model with expressive writing technique based on the philosophy of dandang tingang effective to improve the behavior of respect. Independent test sample T test, from the calculation using SPSS 19.00 application assistance obtained data as follows: T arithmetic (23,703)> T table (2.120) then Ho is rejected and Ha accepted. Therefore it can be concluded that the counseling service group with the technique of expressive writing based on the philosophy of dandang tingang effective to improve the behavior of respect